Learning about author positioning in written academic discourse - Maroko, Geoffrey M. (Argentinian Journal of Applied Linguistics, 2013)
Graduate students are usually not sure of the appropriate stance to take in relation to their writing. Even style guides provide little information regarding authorial positioning in academic texts. This paper describes a study in which frequency and usage of features of marking writer stance were compared between selected dissertations in Kenyan Public Universities. It was found that humanities dissertations preferred personal pronouns and the third person while science dissertations mainly chose the ‘faceless’ agentless passive voice. Suggesting that choices for such features in dissertations are a function of the epistemology and ideology of the disciplines, the paper proposes a genre-based approach to teaching those preparing to write their dissertations.
Keywords: Stance; Disciplinary culture